Análisis financiero en incertidumbre: una propuesta metodológica - Mongrut, Samuel (2004)
One of the tasks that financial managers must accomplish on a regular basis is the financial analysis of the firm. Although there are many tools available within certainty, stochastic and fuzzy paradigms, it is not clear which tools are particularly useful in which paradigms, nor how the tools can be combined to yield more powerful insights. In this work, the authors suggest a methodological framework that will enable managers to identify the most appropriate tool(s) for each paradigm and how to combine them to obtain powerful chains of interrelated tools with which it will be possible to exploit as much as possible the available information.